The role of augmented reality in air accident investigation and practitioner training. (December 2020) - D'Anniballe, A.; Silva, J.; Marzocca, P.; Ceruti, A.
Highlights: Augmented reality has been evaluated as a tool to support air accident investigators and their training. AR has been used to re-create a real aircraft crash scene in a 3D representation. AR has achieved a maturity stage sufficient to support air accident investigators training. Some advances are necessary to increase the effectiveness of AR in aircraft investigations. Abstract: The aim of this paper is to describe the application of digital visualization tools to assist air accident investigators, including both their investigation activities and as a training resource. Augmented Reality technology is used to re-create a real aircraft crash scene, both in terms of wreckage distribution and features of the surroundings, in a full-scale 3D representation. A case study shows both potentials and limitations of the approach, and recommendations on how to improve the methodology are also proposed. Overall, it is concluded that Augmented Reality has achieved a maturity stage sufficient to consider it as an effective tool for training of air accident investigators and, to some extent, to support the investigation process itself, although more developments are required to address some current limitations and fully exploit the capabilities of this technology.